PENGARUH PERAN KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG (PUPR) KARAWANG DI MASA PANDEMI COVID-19 - Luthfi Nur Ahmal (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine, explain, and analyze the partial or simultaneous influence of the role of leadership and organizational culture on employee performance at the Public Works and Spatial Planning Service (PUPR). This type of research is quantitative using descriptive verification method. The population in the study were employees at the Department of Public Works and Spatial Planning (PUPR) totaling 124 people. The sample to be tested in this study amounted to 124 people using the Nonprobability Sampling technique with the Saturated Sampling method. The data analysis technique uses scale range analysis and path analysis and the analytical tool used is SPSS 24 software for windows. Based on the results of the research conducted, it shows that the leadership role gets an average score of 525.2 with good criteria, organizational culture gets an average score of 518.6 with good criteria, employee performance gets an average score of 529.5 with criteria good. The correlation coefficient between the variables of leadership role and organizational culture of 0.734 has a strong, positive and significant correlation level. The partial influence of the leadership role on employee performance is 13.6% while organizational culture on employee performance has a greater influence and contribution, which is 29.5%, simultaneously the total influence of leadership role and organizational culture on employee performance is 72.7% and 27 .3% is another influence that is not measured.